IMPACT OF EMPLOYEE INVOLVEMENT PRACTICES ON ORGANIZATIONAL COMMITMENT - Sharma, Heena; Venkateswaran, C. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to investigate the influence of adopting Employee Involvement Practices comprising of power, rewards, knowledge and information sharing practices on the organizational commitment of the employees. Survey was conducted among the entry level employees working in the private sugar mills of Haryana, based on the logic that entire EI dimensions would be apparent at the minimum level of an organization’s hierarchy, if appropriately executed. The study made use of descriptive research design. Structural Equation Modelling (SEM) was executed for examining the extent to which the proposed conceptual model fits or explains the gathered data. Positive and significant relationship has been found between the EI practices and the commitment of the employees towards their establishment. The hypothesized model fitted the data acceptably. On broad basis, this research added to the literature on strategic human resource management by examining a critical ‘black box’ aspect that connects the Employee Involvement mechanisms to the Organizational Commitment of employees. The current research contributed to the existing literature by examining the Employee Involvement programs adopted by the private sugar mills of Haryana that influenced the commitment of the individuals working there. Hence, the findings of this research would render better illumination of several practices that may enhance the commitment of employees towards their organization.